Short communication: Heterosis and combining ability of Nepalese yellow maize (Zea mays L.) - Gautam, SR; Ojha, BR; Ghimire, SK; Gurung, DB (Agronomy Journal of Nepal, 2013)
Nepalese yellow maize inbred lines were characterized for general combining ability (GCA) and specific combining ability (SCA) of their crosses and parents were identified having high combining ability for determining the heterotic effects on yield and other quantitative traits of hybrids. A line x tester mating design was used for making the crosses in the winter season of 2008 and the hybrids along with their parents and four checks were evaluated in Randomized Complete Block Design (RCBD) with three replications in the spring season of 2009 at the experimental farm of the National Maize Research Program, Chitwan. Significant variations were found among the treatments for grain yield and other traits which indicated presence of high magnitude of genetic variations among tested inbred lines. The cross between RML-32 and RML-17 produced the highest grain yield (15870 kg/ha) among the crosses. Hybrids such as RL-194 x RL-84 (10770 kg/ha), RML-21 x RML-17 (9270 kg/ha), RL-180 x RML-17 (9270 kg/ha) and L-1 x RL-84 (8785 kg/ha) were found superior grain yielder. Thirty-nine hybrids showed positive mid-parent heterosis for grain yield among 40 crosses. The highest positive mid-parent heterosis for grain yield was found 880% in cross between RML-32 and RML-17, followed by RL-98X RML-17 (507%), RL-103 x RML-17 (403%), PUTU-18 x RML- 17 (351%) and RL-180 x RL 84 (316%). Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 172-180 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9020